Use of advanced flap and microsurgery techniques in the resolution of mediastinitis as a complication of cardiac surgery - Ruiz, Rodrigo Banegas; Valderrama Treviño, Alan I.; Gómez Mendoza, Francisco Fabián; Mendoza Aceves, Rodrigo A.; Baca Domínguez, Carlos R.; Hernández, Rigoberto Román; Verdejo, Fernando Gómez; Alba, Ismael Vejar; Ulloa, Rubén Olivares; Ortega, Emilio Pérez; Mera, Baltazar Barrera (International Journal of Research in Medical Sciences, 2019)
In the majority of cases, mediastinitis is a potential complication in any cardiac surgical procedure. The objective of this case report is to accurately describe how the combination of microsurgery and soft tissue flaps can be an effective therapeutic alternative in the treatment of mediastinitis as a complication of cardiac valve replacement. Female 63-year-old patient with a background of obesity, hypertension and extense cardiac interventions, she was programmed for necrosectomy with left pectoralis flap technique. Mediastinitis, although a rare complication of the sternotomy performed in cardiac surgery, occurring in 1-2%, carries a high mortality rate. Early diagnosis of mediastinitis after cardiac surgery requires high clinical suspicion, initially making the diagnosis may be difficult, risk factors should be considered. An early surgical approach can reduce the morbidity and mortality of this condition. The pectoralis flap should be considered as a safe therapeutic option.